The inconsistency of level critical thinking in solving differential equation problem - S S Faradiba; P Andriani; A Alifiani; S E Walida; D Daryono; S N Hasana; A D Angriani; D Chamidah; E Defitriani; M T Qurohman (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Differential equation is a concept that has a variety of solutions that require critical thinking ability. This study explores the Level of Critical Thinking Ability (LCTA) of students in solving differential equation problem. This study is a descriptive qualitative research. The participants of this study were two university students of department of mathematics education, Universitas Islam Malang, who are taking differential equations course. The instruments were critical thinking questions based on IDEAS (Identify, Deepen, Enumerate, Assess, and Scrutinize) criteria and interview guideline. The results of the study showed that the level of critical thinking of students in solving the problem of differential equation is inconsistent. In this case, the inconsistency of the critical thinking level is caused by the obstacles that the students experience when solving the differential equation problem. The student who have problems in solving differential equations will trigger to think critically. It is expected that further research need to be carried out to examine the level of students’ critical thinking in other courses.